The coastal streamflow flux in the Regional Arctic System Model. Issue 3 (4th March 2017) - Hamman, Joseph; Nijssen, Bart; Roberts, Andrew; Craig, Anthony; Maslowski, Wieslaw; Osinski, Robert
Abstract: The coastal streamflow flux from the Arctic drainage basin is an important driver of dynamics in the coupled ice‐ocean system. Comprising more than one third of the total freshwater flux into the Arctic Ocean, streamflow is a key component of the regional and global freshwater cycle. To better represent the coupling of the streamflow flux to the ocean, we have developed and applied the RVIC streamflow routing model within the Regional Arctic System Model (RASM). The RASM is a high‐resolution regional Earth System Model whose domain includes all of the Arctic drainage basin. In this paper, we introduce the RVIC streamflow routing model, detailing its application within RASM and its advancements in terms of representing high‐resolution streamflow processes. We evaluate model simulated streamflow relative to in situ observations and demonstrate a method for improving model performance using a simple optimization procedure. We also present a new, spatially and temporally consistent, high‐resolution data set of coastal freshwater fluxes for the Arctic drainage basin and surrounding areas that is based on a fully coupled RASM simulation and intended for use in Arctic Ocean modeling applications. This data set is evaluated relative to other coastal streamflow data sets commonly used by the ocean modeling community. We demonstrate that the RASM‐simulated streamflow flux better represents the annual cycle than existing data sets, especially in ungauged areas. Finally, we assess the impact that streamflow has on the coupled ice‐ocean system, finding that the presence of streamflow leads to reduced sea surface salinity, increased sea surface temperatures, and decreased sea ice thickness. Key Points: Introduce the RVIC streamflow routing model and its application within RASM Demonstrate the role of the coastal streamflow flux within the coupled model Introduce a new, high‐resolution, coastal freshwater data set for use in ocean modeling applications